Infrastructure and spatial effects on the frequency of cyclist-motorist collisions in the Copenhagen region - Prato, Carlo G.; Kaplan, Sigal; Rasmussen, Thomas K.; Hels, Tove (Proceedings from the Annual Transport Conference at Aalborg University, 2014)
Promoting cycling aims at reducing congestion and pollution and encouraging healthy and sustainable lifestyles, but generally clashes with the perception of crash risk while riding a bicycle that is still the most significant disincentive to cycling. The current study analyzed the factors contributing to increase crash risk while riding a bicycle by focusing on the variation of 5349 cyclist-motorist collisions within 269 traffic zones in the Copenhagen Region. The model controlled for traffic exposure for both bicycles and motorized transport modes, evaluated the effects of infrastructure and socio-economic characteristics of the zones, and accounted for heterogeneity and spatial correlation across the zones. A Poisson-lognormal model with second-order CAR priors confirmed the existence of the safety in numbers phenomenon, contradicted previous literature about bicycle facilities not being helpful in reducing crash risk, highlighted the need for Copenhagen-style bicycle paths especially in suburban areas, and emphasized how heterogeneity and spatial correlation play a significant role in explaining the probability of cyclist-motorist crash occurrence.